EFFECT OF SUPPLEMENATION OF PROBIOTIC AND CITRIC ACID TO LAYING HENS DIET ON EGGS QUALITY TRAITS - & Taha, Jasim (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This study was to understand the effect of supplementation probiotic and different levels of citric acid to laying hens diet on eggs quality traits. during five months used 195 laying hens of  lohmann brown, 20 weeks old, being distributed in 15 ground pens (1. 5 × 2 m / pen) , 13 hens / pen, were randomly divided in to six treatments (3 Rep. / Treat.). First treatment was feded a standard laying diet without any additive as control, second treatment was feded diet with Iraqi probiotic 0.25%, third treatment was feded diet with Citric Acid 0.3% while fourth and fifth treatments were fed diets with Iraqi probiotic 0.25% and different levels of Citric Acid 0.3 and 0.45% respectively. The results showed an improvement in the eggs quality traits of hens fed the probiotic  and citric acid, since significantly increase  an achieved in each of eggs weight, shell weight, yolk weight, yolk index, haugh unit and without significant differences in shell thickness and weight of albumin . The effect of addition treatments had been enhanced the eggs quality traits in hens fed a combination addition of probiotic and citric acid compared with hens fed a single addition of probiotic  or citric acid, that means get a synergistic effect between the probiotic and citric acid.